2021
DOI: 10.1007/978-3-030-86478-1_18
|View full text |Cite
|
Sign up to set email alerts
|

Human Impact Induces Shifts in Trophic Composition and Diversity of Consumer Communities in Small Freshwater Ecosystems

Abstract: The current global rates of human impact intensification in freshwater ecosystems and their surroundings have caused an alarming loss of freshwater biodiversity and functioning across multiple trophic levels. Particularly vulnerable to anthropogenic pressures are small water bodies (SWB). However, the majority of the evidence is limited to a single community, especially macroinvertebrates, thus leaving us uncertain about cross-community multitrophic responses of freshwater

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…The differences in LWR parameters of O. niloticus observed in this study may be due to food supply, food variant as well as the water condition (Siddique et al, 2019). LWR parameters affected by availability of food, seasonal changes, health condition among others as well as biological and environmental factors (Getso, 2017;Laurat et al, 2019;Taheri Mirghaed et al, 2021;Buzhdygan, et al, 2022). The condition factor (K) gives information on the physiological condition of fish in relation to its welfare.…”
Section: Condition Factormentioning
confidence: 99%
See 4 more Smart Citations
“…The differences in LWR parameters of O. niloticus observed in this study may be due to food supply, food variant as well as the water condition (Siddique et al, 2019). LWR parameters affected by availability of food, seasonal changes, health condition among others as well as biological and environmental factors (Getso, 2017;Laurat et al, 2019;Taheri Mirghaed et al, 2021;Buzhdygan, et al, 2022). The condition factor (K) gives information on the physiological condition of fish in relation to its welfare.…”
Section: Condition Factormentioning
confidence: 99%
“…The finding of this research also contradict with the finding of (Getso et al, 2017) who reported K value range between 0.52-1.00 in O. niloticus of Wudil river, Kano. Condition factor is influenced by both biotic and abiotic environmental conditions and can be used as an index to assess the status of the aquatic ecosystem in which the fish live (Anene, 2005;Taheri Mirghaed et al, 2021;Buzhdygan et al, 2022). Change in condition factor of fishes could be used to interpret various biological factors such as fatness, food availability, reproductive activities and environmental health (Dadzie et al, 2000;Laurat et al, 2019).…”
Section: Condition Factormentioning
confidence: 99%
See 3 more Smart Citations